Application of Tax Accounting: The role of Earnings Quality moderates Firm Value which is affected by Tax Avoidance, Financial Leverage and Executive Bonus - Bandiyono, Agus; Nurseto, Ian (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this study is to analyze tax avoidance, financial leverage, and executive bonus to firm value with earnings quality as a moderating variable. This study uses panel data (pooled data) with the population used including all companies listed on the Indonesia Stock Exchange in the period 2014 to 2017 selected by purposive sampling which is part of the non-probability sampling method. The selected criteria include companies conducting initial public offerings (IPOs) after January 1, 2010, by eliminating the population of companies which are the financial, banking and property sectors, real estate, building construction, aviation, shipping, oil and gas, and mining, companies that have profit before tax (pre-tax income) is negative, and companies that do not have complete data, namely financial statement data and annual reports for the 2014–2017 period. From the results of this study, it was found that Tax avoidance harms firm value, Financial leverage has a positive effect on firm value, Executive bonus has a positive effect on firm value, Earnings quality does not affect firm value, and Earnings quality strengthens the negative effect of tax avoidance on firm value, Earnings quality does not moderate the effect of financial leverage on firm value, earnings quality does not moderate the effect of executive bonus on firm value.